2019
DOI: 10.20546/ijcmas.2019.810.257
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficients Studies of Some Morphological and Seed Vigour Traits in Barley Cultivars (Hordeum vulgare L.) under Two Sowing Conditions

Abstract: The experimental material comprised of 50 diverse genotypes were sown in randomized block design with three replications in both timely and late sown condition to study correlation and path coefficient for ten quantitative field traits like days to heading, days to maturity, plant height (cm), spike length (cm), number of tillers per meter row, number of grains per spike,1000 grain weight (g), harvest index (%), biological yield (kg/plot), grain yield (kg/plot) and eight seed parameters viz; seedling length (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Direct and indirect effects of these components determined on grain yield at genotypic level are presented in Table 2. The results of path coefficient analysis revealed that days to maturity (0.477) exerted the highest positive direct effect on grain yield followed by 1000-grain weight (0.218), spike length (0.060), plant height (0.041) and number of grains per spike (0.040), which support the findings of Devi et al [10] except for number of tillers per meter however, Kumar et al [9] in their findings mentioned positive direct effect of number of tillers per meter on grain yield. Therefore, these traits could be considered as main components for selection in a breeding program for higher grain yield.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Direct and indirect effects of these components determined on grain yield at genotypic level are presented in Table 2. The results of path coefficient analysis revealed that days to maturity (0.477) exerted the highest positive direct effect on grain yield followed by 1000-grain weight (0.218), spike length (0.060), plant height (0.041) and number of grains per spike (0.040), which support the findings of Devi et al [10] except for number of tillers per meter however, Kumar et al [9] in their findings mentioned positive direct effect of number of tillers per meter on grain yield. Therefore, these traits could be considered as main components for selection in a breeding program for higher grain yield.…”
Section: Resultssupporting
confidence: 85%
“…3 20 and number of grains per spike with effective tillers per meter; and number of grains per spike with 1000-grain weight, thereby indicating that these traits could not be improved simultaneously. Some authors also reported significant positive correlation for days to heading with maturity [8], plant height with spike length [9], days to maturity with days to maturity and spike length; plant height with spike length and number of grains per spike [10]. The negative and significant relation of effective tillers per meter with plant height and number of grains per spike; 1000-grain weight with number of grains per spike also corroborated with the findings of Devi et al [10] under different environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation